2002
DOI: 10.1002/path.1210
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of the INK4a‐ARF gene locus in pleomorphic adenoma of the parotid gland

Abstract: Pleomorphic adenomas of the parotid gland are benign tumours composed of epithelial and mesenchymal cells. The INK4a-ARF (CDKN2A) locus on chromosome 9p21 encodes two tumour suppressor proteins, p16(INK4a) and p14(ARF), which act as upstream regulators of the Rb-CDK4 and p53 pathways. To study the contribution of each pathway in pleomorphic adenomas, this study analysed alterations of p14(ARF), p16(INK4a), p53, and pRb in these tumours. After microdissecting the different histological components, 42 pleomorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 18 publications
1
14
1
1
Order By: Relevance
“…Investigations of this gene in pleomorphic adenoma have shown conflicting results. 27,28 Collectively, however, previous studies suggest that genes involved in the RB1 pathway are likely targets in the development of pleomorphic adenoma. The present findings thus imply that the RB1 pathway is likely to be involved also in the development of soft tissue MMP tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of this gene in pleomorphic adenoma have shown conflicting results. 27,28 Collectively, however, previous studies suggest that genes involved in the RB1 pathway are likely targets in the development of pleomorphic adenoma. The present findings thus imply that the RB1 pathway is likely to be involved also in the development of soft tissue MMP tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies on the Rb pathway in salivary gland tumors have been focused on only adenoid cystic carcinomas and pleomorphic adenomas [18][19][20][21][22]. In this study, we investigated the status of the Rb pathway in salivary gland ACC.…”
Section: Introductionmentioning
confidence: 99%
“…Etges et al (14) reported that pRb expression was absent in three cases of pleomorphic adenoma, two of epithelial myoepithelial carcinoma and one of carcinoma ex pleomorphic adenoma. They concluded that pRb pathway deregulation in salivary gland neoplasms is unrelated to their biological behavior, Weber et al (15) reported that pRb was detected immunohistochemically in 40/42 pleomoprphic adenomas. They indicated that alterations of p14 (ARF) and p16 (INK4a), and also p53 mutations, occurred exclu-(INK4a), and also p53 mutations, occurred exclu-(INK4a), and also p53 mutations, occurred exclusively in the epithelial and transitional components of pleomorphic adenoma supports the theory that these areas are prone to malignant transformation to carcinoma in adenoma.…”
Section: Chondroid Tissue In Pleomorphic Adenomasmentioning
confidence: 99%